Why Do We Buy Traditional Foods?. Issue 6 (17th August 2016) - Contini, Caterina; Boncinelli, Fabio; Casini, Leonardo; Pagnotta, Gabriele; Romano, Caterina; Scozzafava, Gabriele
ABSTRACT: Consumer behavior toward traditional specialties varies according to the cultural context of consumption. It thus becomes crucial to develop marketing strategies that target segments with different levels of familiarity with food. Our article purposes to analyze the purchase drivers of traditional foods known to consumers because of their reiterated consumption. The importance of the product's attributes, the purchasing motivations, and the information channels are studied by applying the CUB model, which utilizes a probabilistic structure that simulates the individual's psychological mechanism in adopting a choice of preference. The case study is that of extra-virgin olive oil in Italy, where this product is a fundamental element of the culinary tradition. The results show that in the ambit of traditional specialties, in contexts of elevated familiarity, the traditional information channels of marketing are less effective and call for strategies based on a more direct connection between consumer and producer.